2020
DOI: 10.1161/jaha.120.016807
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Risk Factors of Cardiac Involvement in COVID‐19

Abstract: Background Increasing studies demonstrated that the cardiac involvements are related to Coronavirus Disease 2019 (COVID‐19). Thus, we investigated the clinical characteristics of COVID‐19 patients and further determined the risk factors for cardiac involvements in them. Methods and Results We analyzed data from 102 consecutive laboratory‐confirmed and hospitalized COVID‐19 patients (52 women; age, 19–87 years). Epidemiological and demographic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 19 publications
6
51
0
10
Order By: Relevance
“…COVID19 patients frequently show significant myocardial damage as evidenced by elevated troponin-I levels, a biomarker of cardiac damage [ 68 , 69 , 70 ]. COVID19 patients may also present other cardiovascular complications, such as myocarditis, acute myocardial infarction, heart failure, arrhythmias, and venous thromboembolic events [ 69 , 71 , 72 ], and almost half of mildly ill COVID19 patients have abnormalities in heart function [ 73 , 74 , 75 , 76 ]. Together these clinical studies suggest that SARS-CoV2 can directly infect cells in the heart.…”
Section: Macrophage Role In Cardiac Inflammation and Cardiac Dysfumentioning
confidence: 99%
“…COVID19 patients frequently show significant myocardial damage as evidenced by elevated troponin-I levels, a biomarker of cardiac damage [ 68 , 69 , 70 ]. COVID19 patients may also present other cardiovascular complications, such as myocarditis, acute myocardial infarction, heart failure, arrhythmias, and venous thromboembolic events [ 69 , 71 , 72 ], and almost half of mildly ill COVID19 patients have abnormalities in heart function [ 73 , 74 , 75 , 76 ]. Together these clinical studies suggest that SARS-CoV2 can directly infect cells in the heart.…”
Section: Macrophage Role In Cardiac Inflammation and Cardiac Dysfumentioning
confidence: 99%
“…Statistically, hypertension (49.3%), diabetes (32.1%), CHD (28.8%) and COPD (8.8%) are common basic diseases in cardiac-injured patients, which are in line with the studies by Xu et al . [35]. Another multivariable logistic regression analysis also deemed CHD as a predictor of cardiac injury [36].…”
Section: Discussionmentioning
confidence: 99%
“…ARDS, AKI and AHI are common clinical complications in COVID-19 patients. A recent univariate analysis included these complications in risk factors for cardiac involvement [35] and meanwhile, Mohamad et al . found that the incidence of AKI and ARDS was positively correlated with the degree of cardiac injury [38].…”
Section: Discussionmentioning
confidence: 99%
“…A massive release of cytokines consequent to T-cell activation (IL-1, IL-10, IL-12, IL-6, IL-7, IFN-γ, TNF-α, CXCL10, CSF, etc.) may lead to direct myocardial fiber injury [ 9 11 , 29 , 41 , 46 , 51 , 52 ]. Cytokines such as TNF and IL-15 can directly induce myocardial fiber dysfunction, leading to stunning of the myocardium and poor contractile function [ 53 ].…”
Section: Cardiovascular Involvement In Covid-19 Patientsmentioning
confidence: 99%